Implementation of school based management in christian religion high school Kupang - Yusuf Elpontus Tanaem (Faculty of Education, Universitas Negeri Yogyakarta, 2023)
This study aims to analyze the implementation of school-based management in the Christian Religion High School (CRHS) Kupang. The method used in this research is a qualitative method with a descriptive approach. The subjects in this study amounted to 3 (three) people consisting of the principal, vice principal and school committee. Data collection techniques used are interviews and documentation. The data analysis technique used is Analysis Interactive which is divided into four parts, namely data collection, data condensation, data presentation and conclusion. The results of the study show that the implementation of school-based management at CRHS Kupang has been carried out in almost all areas of school-based management which are the indicators in this study. CRHS Kupang has carried out school program planning, implemented the learning process, conducted curriculum management, managed personnel, managed facilities, implemented financial management, implemented student services, built good relations with the community, and carried out a good evaluation of school programs. CRHS Kupang still needs to pay attention to managing the school climate.